Determinan Praktik Internet Financual Reporting (IFR) pada Website Pemerintah Daerah Sumatera Barat - Budiman, Alkausar Putra; Agustin, Henri (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to find out the factors that influence internet financial reporting (IFR) on local government websites. In this study, 19 regencies and cities in West Sumatra were used. The data used is from 2015 to 2019. The data analysis method used to prove the correctness of the hypothesis is multiple regression which is processed using SPSS. Based on the results of hypothesis testing, it was found that the type of local government and the characteristics of local government had a negative effect on the amount of internet financial reporting disclosure in 19 regencies and cities in West Sumatra, while the age of the local government had no significant effect on the amount of internet financial reporting disclosure in 19 regencies and cities in West Sumatra.